REE FRACTIONATION DURING GRANITE WEATHERING AND REMOVAL BY WATERS AND SUSPENDED LOADS: SR AND ND ISOTOPIC EVIDENCE - Aubert D.; Stille P.; Probst A. (My University, 2001)
Very few studies deal with REE (rare earth element) mobility within the system soil-soil solution-streamwater. In this article, we try to characterize the fractionation and the migration of the REE in a granite-derived soil system located in a small catchment of the Vosges mountains. ICP-MS and TIMS measurements were performed on both solid samples (''fresh'' granite, soil, and suspended load of the stream) and waters (soil solutions, springwater, and streamwater) to determine their respective REE concentrations and Sr and Nd isotopic compositions. The PAAS-normalized REE pattern of the bedrock is characterized by a strong depletion in HREE (heavy REE) and a negative Eu anomaly (0.46). Similarly, the granite-normalized REE distribution patterns of the soil samples show HREE depletions that become more important with decreasing depth. The correlative behavior between P2O5, Th, and REE with depth indicates that, besides apatite, other phosphate minerals such as monazite are the most important phases controlling the Th and REE budget in the soil profile. On the other hand, at greater depth, zircon seems to be another important mineral phase controlling especially the HREE enrichment as shown by the positive relationship between Zr content and the Yb/Ho ratio. Different grain size fractions show similar REE distribution patterns and are only weakly fractionated, compared with bulk soil sample. However, the finest fraction (0-20 μm) is more enriched in Sr and REE, suggesting a stronger concentration of REE-carrying minerals in this fraction. The suspended and dissolved load of the stream show as a whole an enrichment in HREE if compared with the granite or with the different soil samples. However, compared with the uppermost soil samples, the suspended load is significantly more enriched in HREE. Its REE distribution pattern is more similar to that of the finest fraction of the deeper soil sample and to the ''fresh'' granite. Thus, most probably the REE of the suspended load originated from a source with REE characteristics found in the deep soil horizons. This source might have been situated in the uppermost soil profile, which is actually REE depleted. The weathering process can be compared with a leaching experiment where the waters correspond to the leachate and the soil to the residual phase of the granite. The Sr isotope data indicate that the suspended load originates from the finest soil fraction. The Sr and Nd isotopic data of the suspended load suggest that it contains up to 3% Sr and Nd from apatite and up to 97% from feldspar. Most of the Sr and Nd in the waters originate from apatite leaching or dissolution.